2018
DOI: 10.1016/j.bpj.2017.11.2528
|View full text |Cite
|
Sign up to set email alerts
|

Human ATG3 Binding to Lipid Bilayers. Role of Lipid Geometry and Electric Charge

Abstract: Specific protein-lipid interactions lead to a gradual recruitment of AuTophaGy-related (ATG) proteins to the nascent membrane during autophagosome (AP) formation. ATG3, a key protein in the movement of LC3 towards the isolation membrane, has been proposed to facilitate LC3/GABARAP lipidation in highly curved membranes. In this work we have performed a biophysical study of human ATG3 interaction with membranes containing phosphatidylethanolamine, phosphatidylcholine and anionic phospholipids. We have found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…Among 16 AHs shown in the Table 1 of Drin and Antonny (2010), this motif is present only in α-synuclein, a protein that binds cardiolipin (Nakamura et al, 2008;Robotta et al, 2014;Ryan et al, 2018). However, except proteins listed in the Table 3, this motif is present in the AHs of at least two proteins that interact with cardiolipin but, to the best of our knowledge, are not known to be involved in membrane fission: PmtA from Bradyrhizobium japonicum (Danne et al, 2017a) and ATG3 (Nath et al, 2014;Hervás et al, 2017). Arg14 and Phe21 belong to TABLE 3 | Amphipathic helices of fission-inducing proteins that use cardiolipin as a lipid cofactor.…”
Section: Cardiolipinmentioning
confidence: 99%
See 1 more Smart Citation
“…Among 16 AHs shown in the Table 1 of Drin and Antonny (2010), this motif is present only in α-synuclein, a protein that binds cardiolipin (Nakamura et al, 2008;Robotta et al, 2014;Ryan et al, 2018). However, except proteins listed in the Table 3, this motif is present in the AHs of at least two proteins that interact with cardiolipin but, to the best of our knowledge, are not known to be involved in membrane fission: PmtA from Bradyrhizobium japonicum (Danne et al, 2017a) and ATG3 (Nath et al, 2014;Hervás et al, 2017). Arg14 and Phe21 belong to TABLE 3 | Amphipathic helices of fission-inducing proteins that use cardiolipin as a lipid cofactor.…”
Section: Cardiolipinmentioning
confidence: 99%
“…Amphipathic helix References the (K/R)x 6 (F/Y) motif in the AH of PmtA from B. japonicum (Danne et al, 2017a), whereas Lys11 and Tyr18 belong to the (K/R)x 6 (F/Y) motif in the AH of Atg3 (Hervás et al, 2017). In the AH of cardiolipin-binding fission-inducing protein PmtA from A. tumefaciens (Danne et al, 2017b), both Lys12 and Phe19 belonging to the Kx 6 F motif are critical for membrane binding (Danne et al, 2015).…”
Section: Proteinmentioning
confidence: 99%
“…Previous studies have identified two ubiquitin‐like modification systems, Atg7–Atg3–Atg8 and Atg5–Atg12–Atg16, which synergistically conjugate Atg8 to PE 15 . It is also well known that Atg3, the E2‐like enzyme, transfers Atg8 to phagophore via binding of its NH domain to the highly curved membrane structures 21,23 . In this study, our results suggest that in addition to the membrane interaction, Atg3 attenuates lipid diffusion while simultaneously enriches local PE concentration to promote Atg8 conjugation to PE.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the increased concentration of PE caused by Atg3 may account for the ability of Atg3 in promoting Atg8 lipidation. Although direct evidence for the interaction between Atg3 and PE is currently lacking, we assume that Atg3 functions via deforming the membranes, 21,43 which leads to lipid arrangement and PE enrichment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation